Manuscripts and Archives : Comparative Views on Record-Keeping. - Bausi, Alessandro; Brockmann, Christian; Friedrich, Michael; Kienitz, Sabine (Berlin/Boston : Walter de Gruyter GmbH, 2018)
The series publishes monographs and collective volumes contributing to the emerging field of manuscript studies (manuscriptology), which includes disciplines such as philology, palaeography, codicology, art history, and material analysis. SMC encourages comparative approaches, without geographical or other limitations on the material studied; it contributes to a historical and systematic survey of manuscript cultures, and provides a new foundation for current discussions in Cultural Studies.
Intro -- Contents -- Preface -- Prologue: Contemporary Practices of Archiving -- How to Distinguish between Manuscripts and Archival Records: A Study in Archival Theory -- Archives from Tibet and the Himalayan Borderlands: Notes on Form and Content -- The Ancient World up to Late Antiquity -- Constitution, Contents, Filing and Use of Private Archives: The Case of Old Assyrian Archives (nineteenth century BCE) -- Archives in Ancient Egypt, 2500-1000 BCE -- Archives and Libraries in Greco-Roman Egypt -- Libraries and Archives in the Former Han Dynasty (206 BCE-9 CE): Arguing for a Distinction -- Setting a Bishopric / Arranging an Archive: Traces of Archival Activity in the Bishopric of Alexandria and Antioch -- Documents, Acts and Archival Habits in Early Christian Church Councils: A Case Study -- The Middle Ages -- Weighing in on Evidence: Documents and Literary Manuscripts in Early Medieval Japan -- Securing and Preserving Written Documents in Byzantium -- Archival Practices in the Muslim World prior to 1500 -- The Power of the Pen: Cadis and their Archives -- Indian Copper-Plate Grants: Inscriptions or Documents? -- Epilogue: Why and how to compare -- Epilogue: Archives and Archiving across Cultures―Towards a Matrix of Analysis -- List of Contributors -- List of Documents.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books